2012
DOI: 10.1103/physrevd.85.014001
|View full text |Cite
|
Sign up to set email alerts
|

Light2++and0++mesons

Abstract: The status of light I ¼ 0, J PC ¼ 2 þþ , and 0 þþ mesons is discussed, particularly the separation of n " n and s " s states. They fall into a simple scheme except for f 2 ð1810Þ. A case is made that this has been confused with the f 0 ð1790Þ. It should be possible to check this with existing or forthcoming data.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
3
16
0
Order By: Relevance
“…Anisovich, et al [8] have used a monopole quark transition form factor to estimate R D = 0.23, which combines with our result to give an η − η ′ mixing angle of φ = 41…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Anisovich, et al [8] have used a monopole quark transition form factor to estimate R D = 0.23, which combines with our result to give an η − η ′ mixing angle of φ = 41…”
Section: Discussionsupporting
confidence: 74%
“…Most notably, exclusive D s decays to the dominant modes (φeν, ηeν, η ′ eν) involve no light valence quarks and thus provide an ideal opportunity for comparisons to lattice QCD results [1,2]. Additionally, since the D s primarily couples to the final state hadron's ss component, D s decay rates can probe the quark content of η − η ′ [3,4] and of the scalar f 0 [5][6][7] (including possible glue components [8,9]). …”
Section: Introductionmentioning
confidence: 99%
“…Many models were proposed in order to resolve this puzzle. It was shown that by including the mentioned hypothetical exotic state as well as the ππ final state interaction, one can describe all the data of the Υ (nS) → Υ (mS)ππ (n > m, n = 2, 3) transitions well [12,13]. Later on, it was shown that the double-bump structure of the dipion invariant mass spectra of the transitions Υ (4S) → Υ (1S, 2S)ππ can also be described with the same exotic particle [14].…”
Section: Introductionmentioning
confidence: 99%
“…[92] made a remark on the status of the state f 2 (1810) such that the state may be confuse with f 0 (1790). [92] has made note, if there was not any confusion between f 2 (1810) and f 0 (1790) there should missing 0 ++ state. As we observed throughout our calculated results, all states (except few states) are underestimated approximate 20 to 40 MeV.…”
Section: Resultsmentioning
confidence: 99%